THE EFFECT OF GROSS REGIONAL DOMESTIC PRODUCT AND THE RATE OF OPEN UNEMPLOYMENT - Abd. Hamid; Yahya; Muhammad Yusuf (Journal of Islamic, Social, Economics and Development, 2018)
This research aims to determine the effect of (1) Gross Regional Domestic Product and the rate of open unemployment to poverty level, (2) Gross Regional Domestic Product to poverty level, (3) the rate of open unemployment to poverty level, and (4) Gross Regional Domestic Product on the rate of open unemployment in Banyuasin Regency, South Sumatra Province, Indonesia. The objective of this research is to investigate the gross regional domestic product influenced the poverty and unemployment in Banyuasin Regency. This research uses a causal quantitative research design. The subjects of this research are Banyuasin Regency, and the object are Gross Regional Domestic Product, the rate of open unemployment, and poverty level. The time series data from 2010-2015 using monthly data. The data collected is using document recording technique. The data were analysed by using path analysis by SPSS. The results of this research showed that (1) there was an effect of Gross Regional Domestic Product and the rate of open unemployment to poverty level is 64.4 percent contribution, (2) there is influence from Gross Regional Domestic Product to poverty level is 47.1 percent contribution, (3) the influence from rate of open unemployment to poverty level is 7.0 percent contribution, and (4) there is a negative influence of Gross Regional Domestic Product on the rate of open unemployment in Banyuasin Regency is 7.4 percent contribution.